A 16S rRNA gene sequencing and analysis protocol for the Illumina MiniSeq platform. Issue 6 (25th March 2018) - Pichler, Monica; Coskun, Ömer K.; Ortega‐Arbulú, Ana‐Sofia; Conci, Nicola; Wörheide, Gert; Vargas, Sergio; Orsi, William D.
Abstract: High‐throughput sequencing of the 16S rRNA gene on the Illumina platform is commonly used to assess microbial diversity in environmental samples. The MiniSeq, Illumina's latest benchtop sequencer, enables more cost‐efficient DNA sequencing relative to larger Illumina sequencing platforms ( e.g., MiSeq). Here we used a modified custom primer sequencing approach to test the fidelity of the MiniSeq for high‐throughput sequencing of the V4 hypervariable region of 16S rRNA genes from complex communities in environmental samples. To this end, we designed additional sequencing primers that enabled application of a dual‐index barcoding method on the MiniSeq. A mock community was sequenced alongside the environmental samples in four different sequencing runs as a quality control benchmark. We were able to recapture a realistic richness of the mock community in all sequencing runs, and identify meaningful differences in alpha and beta diversity in the environmental samples. Furthermore, rarefaction analysis indicated diversity in many environmental samples was close to saturation. These results show that the MiniSeq can produce similar quantities of high‐quality V4 reads compared to the MiSeq, yet is a cost‐effective option for any laboratory interested in performing high‐throughput 16S rRNA gene sequencing. Abstract : Innovation in next‐generation DNA sequencing technology continues to contribute to the democratization of 16S rRNA gene sequencing, which is now often carried out on the Illumina MiSeq and HiSeq platforms. Here, we describe a 16S rRNA gene sequencing protocol for the latest benchtop high‐throughput sequencer, the Illumina MiniSeq, which provides comparable quantity and quality of data, but at significantly reduced cost compared to larger and more expensive sequencers. This opens the opportunity for smaller labs to perform their own 16S sequencing independently.